The Influence of Consumer Knowledge and Brand Image on the Decision to Become a BTN Syariah Jambi Customer - Fermana, Rachmad; Anita, Efni; Syahrizal, Ahmad (Bertuah Jurnal Syariah dan Ekonomi Islam, 2024)
Islamic Bank is a financial institution that runs its business activities based on Islamic principles and sharia. The decision to become a customer of an Islamic bank can be influenced by several factors, including consumer knowledge and brand image. This study aims to determine the simultaneous and partial influence of consumer knowledge and brand image on the decision to become a customer of BTN Syariah Jambi. The sample from this research was 80 customers of the BTN Syariah Jambi. The research results show that consumer knowledge (X1) and brand image (X2) simultaneously have a significant influence on customer decisions. This is proven by the Adjusted R square (coefficient of determination) value of 88,6%.